Antibiotics from Gram-negative bacteria: a comprehensive overview and selected biosynthetic highlights. Issue 7 (26th June 2017) - Masschelein, J.; Jenner, M.; Challis, G. L.
Abstract : Gram-negative bacteria are a rich and underexplored source of antibiotics that are assembled via remarkably diverse biosynthetic pathways. Abstract : Covering: up to 2017 The overwhelming majority of antibiotics in clinical use originate from Gram-positive Actinobacteria. In recent years, however, Gram-negative bacteria have become increasingly recognised as a rich yet underexplored source of novel antimicrobials, with the potential to combat the looming health threat posed by antibiotic resistance. In this article, we have compiled a comprehensive list of natural products with antimicrobial activity from Gram-negative bacteria, including information on their biosynthetic origin(s) and molecular target(s), where known. We also provide a detailed discussion of several unusual pathways for antibiotic biosynthesis in Gram-negative bacteria, serving to highlight the exceptional biocatalytic repertoire of this group of microorganisms.